De-Monopolization toward Long-Term Prosperity in China - Ahuja, Ashvin (Washington, D.C. : International Monetary Fund, 2012)
During the past decade, the average Chinese earns roughly 9 times less and is 10 times less productive than the average American at purchasing power parity. Current consensus attributes large differences in output per worker to differences in total factor productivity (TFP). Evidence suggests that most of the US-China TFP differences lie in the inefficiency of China's domestic-oriented service and agricultural sectors. This paper focuses on (1) the evidence of monopoly rights and its influence on work practice improvement at China's firms and plants and (2) the evidence that policy arrangement there has encouraged more competition in merchandise manufacturing and heavy industries while barriers to market access remain high against new firms in the domestic market (especially in services). A numerical experiment is provided, which suggests that China can enhance long-term income per capita by a factor of 10 largely through TFP gains by implementing reform to weaken protection of monopolies and encourage entry in all industries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet